Multifocal intraocular lenses and retinal diseases - Grzybowski, Andrzej (Graefes Arch Clin Exp Ophthalmol, 2020)
PURPOSE: Multifocal intraocular lenses (MIOLs) are often discouraged in patients with or at risk of retinal disorders (including diabetic retinopathy, age-related macular degeneration, and epiretinal membranes), as MIOLs are believed to reduce contrast sensitivity (CS). Concerns with MIOLs have also been raised in individuals with visual field defects, fixation instability or eccentric preferred retinal locations. The aim of this study is to review the influence of MIOL on quality of vision in patients with retinal diseases. METHODS: We reviewed the PubMed and Web of Science databases to identify relevant studies using the following keywords: multifocal intraocular lens, cataract surgery, cataract extraction, lens exchange, diabetic retinopathy, age-related macular degeneration, and contrast sensitivity. RESULTS: Studies evaluating CS in MIOLs present conflicting results: MIOLs either did not influence CS or resulted in worse performance under low-illuminance conditions and higher spatial frequencies when compared to monofocal IOLs. Nevertheless, MIOLs preserved CS levels within the age-matched normal range. Two studies reported that patients with concurrent retinal diseases receiving a MIOL, both unilaterally and bilaterally, reported a significant improvement in visual-related outcomes. Individuals with a monofocal IOL in one eye and a MIOL in the fellow eye reported greater subjective satisfaction with the MIOL. CONCLUSION: We were unable to find evidence suggesting that patients with retinal diseases should be advised against MIOLs. Nevertheless, more research is needed to address the aforementioned concerns and to optimize the use of MIOLs in eyes with retinal disease. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00417-020-04603-0) contains supplementary material, which is available to authorized users.